PEMBERIAN LIQUID ORGANIC FERTILIZER (LOF) TERHADAP PERTUMBUHAN SENGON (Paraserianthes falcataria (L) Nielsen) (Influence of Liquid Organic Fertilizer (LOF) on Sengon (Paraserianthes falcataria (L) Nielsen) Growth): Yudha1 , Sosilawaty1 dan M. Nababan 2 - Journal, Administrator (Jurnal Hutan Tropika, 2018)
ABSTRACTIn agriculture, the use of waste and garbage organics and seasonings are often used tomake liquid organic fertilizer (LOF), but the making and the using of this LOF in theforestry is still very rare. The objectives of this study were to determine the influence ofliquid organic fertilizer (LOF) on Sengon growth and to find out the best LOF dose forSengon growth. The raw materials of LOF in this study were black sugarcane water, oldcoconut water, rice washing water, Sasa seasoning, fruits peel, Kepok banana hump,Petung bamboo shoots, and shrimp paste. This study used a Completely RandomizedDesign (CRD) with a total experimental unit of 200 Sengon seedlings divided into 5treatments and each treatment consisted of 40 replications. The five treatments were P1(Control, 0 ml LOF), P2 (10 ml LOF + 2 liters of water), P3 (20 ml LOF + 2 liters ofwater), P4 (30 ml LOF + 2 liters of water), and P5 (LOF 40 ml + 2 liters of water). Theresults showed that the influence of liquid organic fertilizer (LOF) had a very significanteffect on each dose treatment on the growth parameters of Sengon seedlings, whichincluded parameters of increase in height, number of leaves and increase in diameter.The treatment of the P5 dose (40 ml + 2 liters of LOF) gave the best influence on thegrowth of Sengon seedlings.Keywords: Liquid organic fertilizer (LOF), sengon